A crisscross-like Fe2N-Ni4N heterostructure with both sulfiphilic and lithiophilic properties enabled high performance lithium-sulfur batteries. Issue 3 (July 2021) - Liu, Jintao; Chen, Junsong; Liu, Xingquan
Abstract: Li-S batteries have been recognized as one of the most promising candidates for next-generation energy storage systems, however, their practically commercialized applications are severely hindered by the shuttle effect of lithium polysulfides (LiPSS ), retarded conversion kinetics and the growth of lithium dendrites. Herein, a vertically growing layered NiFe-LDH derived Ni4 N-Fe2 N heterostructure cross-like nanoarrays on a carbon cloth (CC) (denoted as CC@Ni4 N-Fe2 N@C) was constructed by a pot of hydrothermal method followed by the subsequent carbon coating and nitridation processes to synchronously tackle the above challenges related to Li-S batteries. This heterostructure presents good sulfiphilic and lithiophilic properties and can be directly used as the host materials both for S and Li. As-expected, this heterostructure exhibits the significantly improved discharge specific capacity, rate performance and cycle stability compared with the single-metal nitrides (CC@Ni4 N@C and CC@Fe2 N@C). The study of the symmetric cells certifies that this heterostructure can expose the abundant lithiophilic active sites to achieve the homogeneous Li deposition and effectively suppress the growth of Li dendrites.